SANKSI PIDANA BAGI PELAKU PERKAWINAN ANAK DIBAWAH UMUR DI INDONESIA - Zakki Mubarok; Zenda Vidya Uttamo (Smart Law Journal, 2023)
Juridically, child marriage is a form of violence against children which violates children's rights and is contrary to the State's commitment to protect children from violence and discrimination. In Indonesia, marriage is regulated in Law Number 16 of 2019 Amendments to Law Number 1 of 1974 concerning Marriage which regulates the minimum age limit for a person to marry. In fact, we often find minors getting married, even though they do not meet these criteria. Various reasons were put forward, ranging from economic, social, low education, culture and even incidents of being pregnant first. Through normative legal research with qualitative analysis, this paper describes the high number of child marriages in Indonesia. Based on data from the Central Statistics Agency (BPS) for 2020 child marriage shows a rate of 10.82% in Indonesia. Children who are married under the age of 18 are very vulnerable to various problems. As a result of child marriage, it causes losses not only to children and their families, but also to the State. Child marriage has implications for education, the economy, health, domestic violence and even human trafficking and has the potential to cause intergenerational poverty. Efforts to eliminate child marriage are the target of SDGs point 5.3 in 2030. For this reason, a prevention strategy is needed so that child marriage does not occur, so that child-friendly cities are created in Indonesia. The results showed that: underage child marriages indicated violations of several regulations, namely, the Marriage Law, the Child Protection Law and Article 288 of the Criminal Code. Even though indications of several violations have been found, until now there have been no strict, clear and written regulations regarding sanctions for perpetrators of underage child marriages, only the consequences arising from underage child marriages are subject to criminal sanctions contained in the Article 288 of the Criminal Code. Recognizing the need to enact written laws and regulations, the Ministry of Religion drafted a Draft Law on Applied Law for the Religious Courts which aims to prevent underage child marriages. This draft law provides for fines of up to Rp. 6,000,000.- (six million rupiah) to the perpetrators of underage child marriage and imprisonment for 3 months plus a fine of Rp. 12,000,000 (twelve million rupiah) for the headman who is married.